2015
DOI: 10.1021/acs.biomac.5b01452
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Bundle-Forming α-Helical Peptide–Dendron Hybrids

Abstract: Dendronized helix bundle assemblies combine the sequence diversity and folding properties of proteins with the tailored physical properties of dendrimers. Assembly of peptide-dendron hybrids into α-helical bundles encapsulates the helix bundle motif in a dendritic sheath that will allow the functional, protein-like domain to be transplanted to non-biological environments. A bioorthogonal graft-to synthetic strategy for preparing helix bundle-forming peptide-dendron hybrids is described herein for hybrids 1a, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Molecular self-assembly has been widely utilized to create nanostructured soft matter for applications in biomedicine as well as in electronics and optics. [1][2][3][4][5][6] In stimulus-responsive materials, molecular ordering can give rise to novel modes of activity. For example, the photoisomerization of azobenzene (AZO) motifs is used to generate dimension changes within aligned liquid crystalline (LC) networks.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular self-assembly has been widely utilized to create nanostructured soft matter for applications in biomedicine as well as in electronics and optics. [1][2][3][4][5][6] In stimulus-responsive materials, molecular ordering can give rise to novel modes of activity. For example, the photoisomerization of azobenzene (AZO) motifs is used to generate dimension changes within aligned liquid crystalline (LC) networks.…”
Section: Introductionmentioning
confidence: 99%
“…The same polar and non-polar residues were used in our previously reported α-helical bundle-forming peptide-dendron hybrids. 32, 33, 54, 55 The side-chain amino group of each lysine residue is efficiently acylated using dendritic pentafluorophenyl esters. 54 DeGrado and Lear have shown that a seven-residue peptide with alternating leucine and lysine residues self-assembles into a β-sheet structure in buffered aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Rudimentary protein design rules offer a foundation from which to construct functional materials via programmable hierarchical organization of peptide-dendron hybrids. The recent report of self-organizable α-helix bundle-forming peptide-dendron hybrids 32, 33, 54, 55 is a promising starting point because natural helix bundles exhibit diverse functionality. 67, 68 Indeed, functional hybrid materials based on α-helix bundle-forming peptide-polymer conjugates have validated the concept of designing binding sites for light-harvesting chromophores in polymeric films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations